2015
DOI: 10.1080/07294360.2015.1024626
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing students’ perceptions of graduate attribute acquisition in a multidisciplinary honours track in a Dutch university

Abstract: This article studies the relationship between students' perceptions of teaching and learning in a multidisciplinary honours programme and their impact on graduate attributes acquisition. The study, conducted among 73 honours students in a Dutch research university, evaluates perceived improvement in graduate attributes through annually collected survey data pertaining to student motivation, perception of the teaching and learning environment, engagement in the programme and registered course marks. The evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…This was associated with lack of home support by parents and collaboration with lecturers reducing one's motivation for learning immensely. These results are consistent with findings from studies conducted by Chau-Klu, Rudowicz, Graeme, Xiao Dong, and Kwan (2001); Jansen and Suhre (2015); Lederer, (2007). The studies confirmed that, personal motivation, family background and social class sometimes hindered the development of critical thinking of students during their training and at work.…”
Section: Discussion Of Findingssupporting
confidence: 82%
See 1 more Smart Citation
“…This was associated with lack of home support by parents and collaboration with lecturers reducing one's motivation for learning immensely. These results are consistent with findings from studies conducted by Chau-Klu, Rudowicz, Graeme, Xiao Dong, and Kwan (2001); Jansen and Suhre (2015); Lederer, (2007). The studies confirmed that, personal motivation, family background and social class sometimes hindered the development of critical thinking of students during their training and at work.…”
Section: Discussion Of Findingssupporting
confidence: 82%
“…Brunt (2005) found that there is a relationship between application of critical thinking skills and academic success. Again, Jansen and Suhre (2015) found that students motivation, amount of teacher support in creative and critical thinking, and students' personal inclination to what they are learning provides a crucial role in develping critical thinking among college students.…”
Section: Related Workmentioning
confidence: 99%
“…This implies that when evaluating the programmes, a sole focus on academic achievement may provide an incomplete picture. Indeed, Jansen and Suhre (2015) showed that according to Dutch honours students, the honours programme contributed strongly to their skill development, especially to their research and communication skills. Additionally, Shushok (2003) reported larger self-perceived gains in liberal arts and sciences and technology in honours compared to non-honours students, but no difference in terms of self-reported gains in critical thinking and analytical skills.…”
Section: Effects Of Honours Educationmentioning
confidence: 99%
“…Allan (2011), for example, asked honours students in an interview to reflect on their past year in the programme. Jansen and Suhre (2015) applied a similar approach, using questionnaires to measure motivation and perceived graduate attributes of honours students retrospectively. Both studies concluded that students benefitted from the programmes.…”
Section: Effects Of Honours Educationmentioning
confidence: 99%
“…In an honours learning environment there is a broadening of cooperation in comparison with the student's own study programme, either in a multidisciplinary or an international context (Jansen & Suhre, 2015;Janssen, 2017;Veerman, Kingma, Van Alphen, Smits, & Jukema, 2017). Multidisciplinary connections are important to solve complex problems.…”
Section: Multidisciplinary Connectionsmentioning
confidence: 99%